Kibbutzniks in the diaspora - Sabar, Naama (SUNY series in Israeli studies., 2000)
"Under what circumstance would kibbutz-born young people leave a society which symbolizes, more than anything else, the Zionist dream? Naama Sabar explores this question by examining the lives of a group of Israeli emigrants living in Los Angeles in the 1980s and early 1990s. Through extensive interviews in which these "kibbutzniks" share their life stories, she uncovers what pushed them to leave the kibbutz and what pulls them to remain in L.A. The underlying leitmotif is the search for identity under changing conditions."--Jacket.